Gastric decontamination–a view for the millennium. Issue 2 (1st March 1999) - Bateman, D N
Abstract : The management of acute poisoning remains an important part of accident and emergency (A&E) care. Three gastric decontamination procedures have been widely used: gastric lavage, ipecac, and activated charcoal. Their role has recently been reviewed and position statements developed by working groups of the American Academy of Clinical Toxicology and the European Association of Poisons Centres and Clinical Toxicologists. These have important implications for A&E, as they indicate that activated charcoal is now the agent of choice for most poisons, but than in most situations it is probably only effective if given within an hour of overdose. Ipecac is effectively obsolete and gastric lavage has a narrow range of indications, principally for potentially serious amounts of agents not adsorbed by charcoal. Protocols for care of overdose patients should be modified accordingly.